The Canonical Tradition Valuing the Right to Reputation - Mazza, Michael Joseph (Revista española de derecho canónico, 2022)
The right to a good name is a fundamental, natural human right that is mentioned specifically in canon 220 of the 1983 Code. In the present environment, however, this right has been frequently forgotten. Catholic clergy, in particular, have seen their right to reputation overlooked by forces both within and outside the Church. This article shows that respect for the good of bona fama is fundamental to any truly human community. Noting the impressive canonical tradition strongly in support of the juridical good of bona fama, this article demonstrates how the good of bona fama became part of the lived testimony of the early Church and developed over time. The canonical tradition was incorporated into the Church's first attempt at codification in 1917; the reform of that Code after Vatican II clearly reflected the developments in 20th century magisterial teaching on the good of reputation.